Scholarly and Economic Empowerment of Women in early Islamic Era - Dr. Muhammad Saeed Akhter, Dr. Muhammad Nasir (Journal of Research in Humanities, 2023)
This paper rests on the assumption that Islam, in essence, is a socio-political and economic movement that strives to establish a society based on the principles of justice, peace and economic prosperity. It reveals how, in the early Islamic phase, this movement, true to its spirit emancipated and enabled not only men, but women also. It empowered women, lifted them out of ignorance and gave them education and through them spread it. Not only that, but Islam accepted their right to earn and facilitated them to play an active role in society. Thus, the paper looks at scholarly and economic empowerment of women in early Islamic era. The paper cites the most authentic sources from the Islamic tradition of scholarship to establish its case and implies that any effort to show that Islam does not believe in emancipation and empowerment of women can be easily rebutted by harking back to the initial Islamic era